Interventional neuroradiology of the spine : clinical features, diagnosis and therapy - Muto, Mario (Springer Milan, 2013)
Accurate interpretation of indications for treatment is the cornerstone of success in medicine. This book carefully examines the relation between clinical features, diagnosis, and choice of minimally invasive technique for a range of spine pathologies. It explains how selection of technique is intimately related to clinical and diagnostic aspects and how recognition of this relation forms the foundation for an optimal outcome. In addition to examining the various minimally invasive options, including the latest techniques, careful attention is paid to the role of medical treatment in avoiding recurrence after initial therapy. Nerve blocks, epidural injections, and intradiscal procedures are among the many options available in the armamentarium of the interventionalist, and advice is given on their use in different contexts. This volume will be of great value for neuroradiologists and others responsible for treating patients with spine disorders.